Conjugated polyelectrolytes : fundamentals and applications - Liu, Bin; Bazan, G. (Wiley-VCH, 2013)
"This is the first monograph to specifically focus on fundamentals and applications of polyelectrolytes, a class of molecules that gained substantial interest due to their unique combination of properties. Combining both features of organic semiconductors and polyelectrolytes, they offer a broad field for fundamental research as well as applications to analytical chemistry, optical imaging, and opto-electronic devices. The initial chapters introduce readers to the synthesis, optical and electrical properties of various conjugated polyelectrolytes. This is followed by chapters on the applications of these materials in optical sensing and imaging with emphasis on biological systems, while the final section addresses the emerging applications of conjugated polyelectrolytes in optoelectronic devices, concluding with an in-depth discussion of structure-property relationship. The editors and contributors are all pioneers and experts in this expanding field. This monograph is not only for chemists, materials scientists, and physicists, but also a unique source of knowledge for readers with scientific background interested in polyelectrolytes."--